2010
DOI: 10.1136/gut.2010.223602
|View full text |Cite
|
Sign up to set email alerts
|

Sequential DNA methylation changes are associated with DNMT3B overexpression in colorectal neoplastic progression

Abstract: Hierarchical epigenetic alterations occur at transition points during colorectal neoplastic progression. These cumulative changes are closely correlated with a gain of DNMT3B expression, suggesting a causal relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 54 publications
7
102
1
Order By: Relevance
“…In PPARG-negative cells, UHRF1 is, in fact, recruited on the PPARG promoter where it interacts with other regulatory factors required for DNA and histone methylation. In agreement with the data in the literature, DNMT3b is recruited on the PPARG promoter providing support to its involvement in gene repression and colon tumorigenesis (Linhart et al, 2007;Nosho et al, 2009;Ibrahim et al, 2011). DNMT1 and DNMT3a seem to have a lower impact on PPARG silencing as they are not recruited on the promoter; the differential recruitment of DNMT3a may reflect the very low protein levels detected in the cells analyzed.…”
Section: Discussionsupporting
confidence: 78%
“…In PPARG-negative cells, UHRF1 is, in fact, recruited on the PPARG promoter where it interacts with other regulatory factors required for DNA and histone methylation. In agreement with the data in the literature, DNMT3b is recruited on the PPARG promoter providing support to its involvement in gene repression and colon tumorigenesis (Linhart et al, 2007;Nosho et al, 2009;Ibrahim et al, 2011). DNMT1 and DNMT3a seem to have a lower impact on PPARG silencing as they are not recruited on the promoter; the differential recruitment of DNMT3a may reflect the very low protein levels detected in the cells analyzed.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the efficiency of DNA methylation may be affected by age (12,29). Finally, neoplasia may induce "field-effect" hypomethylation in cancer and surrounding histologically normal tissues, through sequestration of DNA methylation enzymes and substrates by rapidly proliferating, dividing cancer cells, resulting in failure of DNA methylation maintenance in surrounding tissue (11,(30)(31)(32)(33)(34)(35).…”
Section: Causes and Consequences Of Genome-wide Hypomethylationmentioning
confidence: 99%
“…13 Previous studies have shown a significant increase in DNMT3B enzyme from the normal epithelium to hyperplastic one and from hyperplastic epithelium to carcinoma. 8 This significant finding related to the DNA hypermethylation can be observed in the sub-panel of CIMP, including CAC-NA1G, NEUROG1, CDKN2A, and hMLH1 genes. Increased amount of DNMT3B mRNA in colon cancer tissues, in comparison with normal tissues, is shown in several studies.…”
Section: Introductionmentioning
confidence: 93%
“…The modified pattern of DNA methylation can alter the expression of genes associated with cancer. 8 Decreased global DNA methylation, seen in the malignancy process, alters genomic stability too.…”
Section: Introductionmentioning
confidence: 99%